(untitled) (Pakistan Journal of Science, 2022)
The present study was carried out to determine the prevalence of Fasciola Hepatica in sheep and goats of Dera Ismail Khan. In this respect faeces and blood samples of 380 sheep and 400 goats were screened to identify 100 infected animals (50 sheep, group-A) and 50 goats, group-B) positive for fascioliasis. Haemoglobin level, packed cell volume, total leukocyte count, differential leukocyte count and total blood serum protein were studied for the positive animals. The faecal examination showed 13.39% and 12.50% fascioliasis in sheep and goats, respectively. On an average Group A and B were attaining 650 and 750 Eggs Per Gram (EPG), 8.67 and 8.15 million/cmm Total Erythrocytic Count, 23.95% and 25.50% Packed Cell Volume, 7.25 and 7.15 g/100ml haemoglobin level of blood, 6.25 x 103 /cmm and 7.39 x 103/cmm Total Leukocyte Count, 5.76 and 5.68 g/100 ml Total Serum Protein, respectively. There was no deviation in monocytes percentage than the normal range. It was concluded that Fascioliasis in sheep and goat in district D.I.Khan is considerable threat for the health and production of animals as well as a cause for poor mutton quality from infested sheep and goats.